Wind farm flow control oriented to electricity markets and grid integration: Initial perspective analysis. Issue 3 (21st June 2021) - Eguinoa, Irene; Göçmen, Tuhfe; Garcia‐Rosa, Paula B.; Das, Kaushik; Petrović, Vlaho; Kölle, Konstanze; Manjock, Andreas; Koivisto, Matti J.; Smailes, Michael
Abstract: Wind farm control (WFC) allows coordinated operation of the wind turbines within a wind power plant (WPP). However, its development has traditionally been split into the distinct disciplines of power plant control and farm flow control. As variable renewable energies, in particular wind energy, increase their penetration into the power system, grid code requirements become stricter for WPPs and electricity markets necessarily evolve. In such a context, crossfertilization between the two categories of WFC, targeting an integrated approach where applicable, becomes a priority. An initial overview on how to further align wind farm flow control (WFFC) to grid and electricity markets participation is provided, including an analysis of capabilities and prospects. In addition, greater detail is given about an open‐access dataset serving as market showcases for value demonstration of price‐driven operation of WPPs by means of WFFC. Abstract : An initial overview is provided on how to further align wind farm flow control (WFFC) to grid integration and electricity markets participation. An analysis of current WFFC capabilities and challenges is performed, including the certification of the technology. Prospects are also outlined for value creation targeting specific ancillary services. In addition, greater detail is given about an openaccess dataset serving as market showcases for value demonstration of price‐driven operation of wind power plants (WPPs) by means of WFFC.